How to construct an improved feeding trough - Gosling, Amanda; Center for International Forestry Research and World Agroforestry (2024)
This poster explains the benefits of adopting the improved feeding troughs designed by the Africa RISING project. It gives tips on constructing the troughs, with the recommended designs and measurements. The poster forms part of the Climate-Smart Forage and Feed Innovations training package that was co-developed with the Center for International Forestry Research and World Agroforestry (CIFOR-ICRAF) Tanzania and Malawi teams to accelerate the spillover process of validated AICCRA technologies. The poster content was sourced from the AICCRA Ethiopia team.